The European and Global Dimension of Mountain Research - Axel Borsdorf; Valerie Braun (Revue de Géographie Alpine)
Within the last century the awareness of mountain regions and their complex system has grown and the motivation to protect these regions has yielded numerous initiatives around the globe with the aim of acting internationally and politically as well as joining forces to intensify inter– and transdisciplinarity in scientific work. The challenges of mountain research in the future will be to involve politicians, stakeholders and the mountain population more effectively in order to mitigate the pressures of globalization towards a sustainable regional development within mountain regions. The significance of providing an overview of institutions representing mountainous regions around the globe lies in showing the main focus of the different institutions and the areas they work in.